Penggunaan Katalis CaO Dari Ca(NO3)2 Dengan Support Serbuk Besi Pada Pembuatan Biodiesel Dari Minyak Sawit Off-Grade (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is one of renewable energy that formed as liquid fuel and has same property with petrodiesel. Biodiesel is able to besynthesized from off-grade palm oil using CaO/Wasted iron as catalyst in transesterification process. Employing Wasted iron as support in CaO has a good impact due to environmentally friendly, good economic potential and magnetic separation of the catalyst. Biodiesel production in this study aims is to see the influence of reaction temperature, molar ratio of methanol and oil and concentration of CaO/Wasted iron towards biodiesel yield. The process was conducted through reaction of esterification and followed by transesterification reaction. Processing of the data in this study was conducted by response surface methodology (RSM) using Design Expert 7.0 program which is experimental design determined by central composite design (CCD) which consists of three variables. The highest result of biodiesel yield was 67,64% at 70oC reaction temperature, molar ratio of methanol : oil 6 : 1 and catalyst concentration of CaO/Wasted iron 3%-w. Biodiesel characteristics like as density, kinematic viscosity, acid value and flash point has been appropriate by Indonesian biodiesel standard. The most significant process condition affecting the yield of biodiesel was catalyst concentration.Keywords :biodiesel, catalyst, off-grade palm oil, transesterification, wasted iron.